2018
DOI: 10.1038/s41598-018-29462-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic regulation of disease risk and endometrial gene expression highlights potential target genes for endometriosis and polycystic ovarian syndrome

Abstract: Gene expression varies markedly across the menstrual cycle and expression levels for many genes are under genetic control. We analyzed gene expression and mapped expression quantitative trait loci (eQTLs) in endometrial tissue samples from 229 women and then analyzed the overlap of endometrial eQTL signals with genomic regions associated with endometriosis and other reproductive traits. We observed a total of 45,923 cis-eQTLs for 417 unique genes and 2,968 trans-eQTLs affecting 82 unique genes. Two eQTLs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(78 citation statements)
references
References 79 publications
(113 reference statements)
2
74
2
Order By: Relevance
“…Whereas some genes exhibit more tissue-specific effects, others have similar effects in a range of tissues (20,61,62). We assessed colocalization using datasets including a wide range of tissue types (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas some genes exhibit more tissue-specific effects, others have similar effects in a range of tissues (20,61,62). We assessed colocalization using datasets including a wide range of tissue types (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…MFAP2 stimulates epithelial–mesenchymal transition in gastric cancer cells by activating TGFβ signaling pathway that supports survival and metastasis of endometrial cancer cells (Lei et al, 2009). MFAP2 is also related to human endometrial receptivity (Díaz-Gimeno et al, 2011) and has been defined as biochemical pregnancy biomarkers (Fung et al, 2018). Other study found MFAP2 as differentially expressed in severe vs. mild endometriosis (Fung et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…MFAP2 is also related to human endometrial receptivity (Díaz-Gimeno et al, 2011) and has been defined as biochemical pregnancy biomarkers (Fung et al, 2018). Other study found MFAP2 as differentially expressed in severe vs. mild endometriosis (Fung et al, 2018). SMAP2 was reported to be involved in microsatellite instability oncogenesis (Sangar et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Variation in gene expression in human endometrium is strongly influenced by the stage of the menstrual cycle. The global methylation level of eutopic endometrium was reported to be higher in the proliferative phase as compared to the secretory phase of the menstrual cycle [126].…”
Section: Epigenetic Histone Modificationsmentioning
confidence: 99%